USING STORY PYRAMID STRATEGY TO IMPROVE READING COMPREHENSION OF THE EIGHT GRADE STUDENTS OF SMP NEGERI 14 PALU - Herman, Widyawati; Aminah, Aminah; Dewi, Anjar Kusuma (e-Journal of ELTS (English Language Teaching Society), 2025)
This research was conducted at grade eighth students of SMP Negeri 14 Palu in the teaching and learning process. This research aims to improve students' reading comprehension by using the Story Pyramid Strategy. The population in this research was grade eighth students of SMP Negeri 14 Palu. This research employs purposive sampling to select the sample. This research applies a quasi-experimental research design non-equivalent control group design, which consists of two groups: experimental and control group. The description of the data collected through the pre-test and post-test. The students’ scores after presenting the material using Story Pyramid Strategy in reading comprehension were better than before the treatment was given to the student . This strategy can be a learning media applied by teachers in the teaching and learning process as an effective strategy to improve students’ reading comprehension because the use of Story Pyramid Strategy makes it easier for students to understand the content of the story. The result of the data analysis is that t-count was higher than t-table. From these results, the researcher found there is a significant difference between the pre-test and post-test result. This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. This is proven by the improvement of students reading comprehension after being given treatment using story pyramid strategy.